Development and democracy : what have we learned and how? - Elgström, Ole, 1950-; Hydén, Göran, 1938- (London ; New York : Routledge : ECPR, 2003)
This collection confirms the robust relationship between level of economic development and democracy, but suggests that globalization is a key variable in determining the tenuous nature of this relationship.
Book Cover; Title; Contents; List of figures; List of tables; List of contributors; Series editor's preface; Preface and acknowledgements; List of abbreviations; Development and democracy: an overview; Globalisation and democracy: an overlooked connection; Development, class and democracy: is there a relationship?; Transitions to democracy: pros and cons of the Rustow Lijphart elite approach; Development, law and democracy: exploring a new relationship; Modernisation and democracy: electoral systems as intermediate variable; Problems of measuring democracy: illustrations from Africa.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Democracy; Economic development -- Political aspects; Comparative government; Développement économique -- Aspect politique; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Comparative government; Democracy; Economic development -- Political aspects